A deusa dos orixás: Clara Nunes - o som dos terreiros de umbanda e candomblé nos palcos da música popular brasileira - Marçal, Danilo Azevedo Oliveira (2024)
This work aims to create a dialogue between Afro-Brazilian religions and samba from a historical, sociological and anthropological approach. For this, it was necessary to cover as a basis the study of the phenomenology of religion and culture, where I later explored the nuances of the music market and the cultural industry, ending with an outline of the incomparable artistic work and the relevant social and political performance of Clara Nunes. It also shows the valuable contribution of this artist to samba and African religions, also highlighting how her work was gradually modified and adapted to meet the needs of the music market. To construct this study, various aspects of the artist's life, construction and career consecration were also taken into account, as well as temporal elements, social issues and Brazilian structural racism. As it is a study based on phenomenology, the elements, spaces and religious issues during the writing seek to emphasize the great presence of Afro-Brazilian religions in the songs. To do this, it was necessary to analyze the phonograms recorded by the artist with the presence of the Afro-religious universe and samba, in different eras and with changes and transformations in musical genres and styles, and performances on stage. In this way, the research takes place in a debate to espect the importance of the black population for the construction of a Brazilian religious and consequently cultural identity and, nevertheless, the immense legacy left by the Umbanda and Candomblé terreiros for the perpetuation and maintenance of our traditions.